1997
DOI: 10.1097/00007890-199708270-00003
|View full text |Cite
|
Sign up to set email alerts
|

Fat Absorption After Small Intestinal Transplantation in the Rat1

Abstract: These results suggest that in this model of SIT, fat absorption via the mesenteric duct is reduced, but that compensatory collaterals form into the retroperitoneal lymphatics. There was no evidence of any significant increase in portal venous uptake of fatty acids after SIT, nor of preferential absorption of medium-chain fatty acids. These results may have implications for patients after SIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Infusion rates between 2-4 ml/h correspond to physiological flow rates in the rat intestinal lymphatic system. 5,17,18 Serial pictures under standardized injection pressure of the contrast media show the speed of lymphatic drainage. A drawback of lymphography is its requirement for an X-ray machine and the higher costs for material and personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion rates between 2-4 ml/h correspond to physiological flow rates in the rat intestinal lymphatic system. 5,17,18 Serial pictures under standardized injection pressure of the contrast media show the speed of lymphatic drainage. A drawback of lymphography is its requirement for an X-ray machine and the higher costs for material and personnel.…”
Section: Discussionmentioning
confidence: 99%
“…However, measurements of faecal fat concentration instead of daily excretion may not reflect the actual daily absorption of fat very reliably. Normal fat absorption after SBT in rats on a low-fat diet has been repeatedly reported, which certainly should not rule out the possibility of SBT-induced fat malabsorption in other species, including humans (103,133,168). Indeed, Sigalet et al (131) reported a slight but statistically significant decrease in fractional fat absorption in rats 8 weeks after SBAT when both control and SBAT animals received cyclosporin therapy.…”
Section: Physiology Of the Transplanted Jejunoileummentioning
confidence: 99%
“…On the basis of these considerations, excluding the very early postoperative period, lymphatic disruption (and subsequent regeneration) may not have a very essential role in overall lipid absorption after SBT. Recently, Winkelaar et al (168) examined the physiology of the lymphatic system in a rat model of SBAT and found reduced lauric and palmitic acid transport via the mesenteric duct 6 weeks after the operation, although overall fat absorption from the diet of low-fat content was preserved (168). However, compensatory collaterals formed in the retroperitoneal lymphatics, enabling an apparently preserved lymphatic flow of absorbed fat, whereas there was no evidence of any significant increase in portal venous uptake of fatty acids or of preferential uptake of medium-chain fatty acids.…”
Section: Physiology Of the Transplanted Jejunoileummentioning
confidence: 99%
“…The theoretical and experimental basis for fat restriction is the unavoidable disruption of lymphatic channels of the intestinal allograft during the procurement procedure, with the potential risk of fat malabsorption or lymphatic disruption before reconstitution of the lymphatic channels. [33][34][35][36] Clinical data to support such a claim were solely dependent on practical surveys during the early developmental phase of intestinal transplantation. 4,37,38 Yet in each of these surveys, the reported risk of chylous ascites was low, and occurred early after transplantation.…”
Section: Restoration Of Nutrition Autonomymentioning
confidence: 99%